2011
DOI: 10.1016/j.bcp.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenic effects of dietary isothiocyanates: Mechanisms of action and implications for human health

Abstract: To cite this version:Breeze E. Cavell, Sharifah S. Syed Alwi, Alison Donlevy, Graham Packham. Anti-angiogenic effects of dietary isothiocyanates; mechanisms of action and implications for human health. Biochemical Pharmacology, Elsevier, 2010, 81 (3) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 93 publications
1
48
0
1
Order By: Relevance
“…It is rich in benzyl isothiocyanate (BITC) which may provide potential for use in chemoprevention of cancer. It has been suggested that the anti-carcinogenic effects of isothiocyanates are related to their capacity to induce phase II enzymes such as glutathione S-transferase, nicotinamide adenine dinucleotide phosphate and quinine reductase (Cavell et al, 2011;Nakamura et al, 2000). The glucosinolates are known to be degraded into isothiocyanates by enzymatic action of plantspecific myrosinase or intestinal microbiota in the human body (Basu and Haldar, 2008).…”
Section: Fruitmentioning
confidence: 98%
“…It is rich in benzyl isothiocyanate (BITC) which may provide potential for use in chemoprevention of cancer. It has been suggested that the anti-carcinogenic effects of isothiocyanates are related to their capacity to induce phase II enzymes such as glutathione S-transferase, nicotinamide adenine dinucleotide phosphate and quinine reductase (Cavell et al, 2011;Nakamura et al, 2000). The glucosinolates are known to be degraded into isothiocyanates by enzymatic action of plantspecific myrosinase or intestinal microbiota in the human body (Basu and Haldar, 2008).…”
Section: Fruitmentioning
confidence: 98%
“…PEITC has received considerable attention due to its potential chemopreventive and chemotherapeutic activities (Cavell et al 2011;Cheung and Kong 2010;Hayes et al 2008). PEITC decreases carcinogen-induced cancer development in vivo and interferes with the activation of carcinogens via inhibition of phase I metabolism and activation of phase II metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…PHI (LKT Laboratories, Inc., St. Paul, MN, USA), >98% pure, was dissolved in 75% methanol to a stock concentration of 5 mmol/l and stored at -20˚C following positive pressure filtration through a 0. 22 Cell culture. The human AML cell line HL-60 was obtained from the China Center for Type Culture Collection (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Isothiocyanates are best known for their antioxidative, anticancer chemotherapeutic, chemopreventive, and anti-angiogenic properties (21,22). PHI, a synthetic isothiocyanate, is able to induce cell growth arrest and apoptosis in a number of types of tumor cell by inhibiting histone deacetylation, histone methylation and DNA methylation, and by remodeling chromatins (23)(24)(25)(26)(27).…”
Section: Synergistic Effects Of Phenylhexyl Isothiocyanate and Ly294002mentioning
confidence: 99%